2021
DOI: 10.1177/11769343211064616
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Dynamics of Indels in SARS-CoV-2 Spike Glycoprotein

Abstract: SARS-CoV-2, responsible for the current COVID-19 pandemic that claimed over 5.0 million lives, belongs to a class of enveloped viruses that undergo quick evolutionary adjustments under selection pressure. Numerous variants have emerged in SARS-CoV-2, posing a serious challenge to the global vaccination effort and COVID-19 management. The evolutionary dynamics of this virus are only beginning to be explored. In this work, we have analysed 1.79 million spike glycoprotein sequences of SARS-CoV-2 and found that th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Sequence, structural property, and phylogenetic tree analyses of Mibgl3. (a) Alignment of amino acid sequences of Mibgl3, HvExo, BoGH3, AoGH, and EmGH performed using Clustal Omega () and ENDscript server (). , The accession numbers were WP_067196459 for Mibgl3, 1EX1 for HvExoI, 5JP0 for BoGH3, 5YOT for AoGH, and 5Z87 for EmGH1. The amino acid residues that are conserved in all four proteins, are denoted with white letters and highlighted in red.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence, structural property, and phylogenetic tree analyses of Mibgl3. (a) Alignment of amino acid sequences of Mibgl3, HvExo, BoGH3, AoGH, and EmGH performed using Clustal Omega () and ENDscript server (). , The accession numbers were WP_067196459 for Mibgl3, 1EX1 for HvExoI, 5JP0 for BoGH3, 5YOT for AoGH, and 5Z87 for EmGH1. The amino acid residues that are conserved in all four proteins, are denoted with white letters and highlighted in red.…”
Section: Resultsmentioning
confidence: 99%
“…Enzyme annotation was performed by the Carbohydrate Active Enzyme Annotation web server (dbCAN, ) . Alignment of amino acid sequences of different β-glucosidases was performed using Clustal Omega () and the ENDscript server (). , The amino acid sequence of Mibgl3 was submitted to the National Center for Biotechnology Information database, and the BLASTp tool was used for sequence alignment to download amino acid sequences of related GH3 proteins with high homology. Developmental tree mapping and analysis were performed using MEGA 7.0 …”
Section: Methodsmentioning
confidence: 99%
“…Others have called variants with other tools such as DeepSNV (20) and VarScan (21). DeepSNV was not used as it only investigates SNVs (22), when indels have been found to confer selective advantages (23). Freebayes has been observed to perform slightly superiorly than VarScan when calling variants in wastewater samples (24) and in internal benchmarking (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…While highly similar sequences lead to nonspecific primer/probe binding and lead to ambiguous detection of OPVs, highly divergent or variable sequence regions pose considerable challenge to detection. As in other viruses (Rao et al, 2021), comparison among OPVs such as VACV and VARV revealed that indels of 3-25 bp are common events in poxviruses (Coulson and Upton, 2011). The A27L (ATI) gene is one such hypervariable target containing variations including truncations, deletions, insertions, and base changes in the two clades of MPXV (Meyer et al, 1997).…”
Section: Detection Of Mpxv -Challenges and Opportunitiesmentioning
confidence: 99%